Study on the use of antibiotics in patients with upper respiratory tract infections (URI) at a public health center in karawang regency - Ida Lisni; Nurlutfita Arsila; Entris Sutrisno (Journal of Midwifery and Nursing, 2025)
Respiratory Tract Infection is an infection affecting the respiratory tract structures, damaging the gas exchange process from the nose to the alveoli, lasting up to 14 days, and is typically contagious. Upper Respiratory Tract Infection (URTI) is a disease with a high prevalence, causing nearly 4 million deaths each year. This study aims to determine the pattern of antibiotic use and the appropriateness of drug administration based on indications, dosage, and frequency at a health center in Karawang Regency. The research was conducted retrospectively from patient medical records and analyzed quantitatively. The results show that 121 patients in this study used antibiotics. Based on gender, 52.89% were male and 47.10% were female. The most common age category was early adulthood (26-35 years) at 26.44%. The antibiotics used were Amoxicillin (57.02%), Cefixime (22.31%), and Cotrimoxazole (20.66%). The accuracy of drug use with appropriate indications was 100%, the appropriateness of dosage was 99.17%, and the appropriateness of frequency was 100%.